Cross-sectional survey of orthotic service provision in the UK: does where you live affect the service you receive? - Nachiappan Chockalingam; Nicola Eddison; Aoife Healy (BMJ Open)
Objective To investigate the quantity and quality of orthotic service provision within the UK.Design Cross-sectional survey obtained through freedom of information request in 2017.Setting National Health Service (NHS) Trusts/Health Boards (HBs) across the UK.Main outcome measures Descriptive statistics of survey results, including information related to finance, volume of appointments, patients and orthotic products, waiting times, staffing, complaints, outcome measures and key performance indicators.Results Responses were received from 61% (119/196) of contacted Trusts/HBs; 86% response rate from Scotland (12/14) and Wales (6/7), 60% (3/5) from Northern Ireland and 58% (98/170) from England. An inhouse service was provided by 32% (35/110) of responses and 68% (74/110) were funded by a block contract. Long waiting times for appointments and lead times for footwear/orthoses, and large variations in patient entitlements for orthotic products across Trusts/HBs were evident. Variations in the length of appointment times were also evident between regions of the UK and between contracted and inhouse services, with all appointment times relatively short. There was evidence of improvements in service provision; ability for direct general practitioner referral and orthotic services included within multidisciplinary clinics. However, this was not found in all Trusts/HBs.Conclusions The aim to provide a complete UK picture of orthotic service provision was hindered by the low response rate and limited information provided in some responses, with greater ability of Trusts/HBs to answer questions related to quantity of service than those that reflect quality. However, results highlight the large discrepancies in service provision between Trusts/HBs, the gaps in data capture and the need for the UK NHS to establish appropriate processes to record the quantity and quality of orthotic service provision. In addition to standardising appointment times across the NHS, guidelines on product entitlements for patients and their lead times should be prescribed to promote equity.